Surface engineering of Pt surfaces with Au and cobalt oxide nanostructures for enhanced formic acid electro-oxidation - Islam M. Al-Akraa; Yaser M. Asal; Ahmad M. Mohammad (Arabian Journal of Chemistry, 2022)
This study aims to mitigate the CO poisoning of platinum (Pt) surfaces during formic acid electro-oxidation (FAEO), the essential anodic reaction in the direct formic acid fuel cells (DFAFCs). For this purpose, a glassy carbon (GC) electrode was amended sequentially with Pt (n-Pt), gold (n-Au), and cobalt oxide (n-CoOx) nanostructures. Fascinatingly, the ternary modified n-CoOx/n-Au/n-Pt/GC catalyst (for which n-Pt, n-Au, and n-CoOx were sequentially and respectively assembled onto the GC surface) exhibited a remarkable electrocatalytic enhancement toward FAEO, which surpassed ca. 53 times that of the Pt/GC catalyst. Additionally, it exhibited a much (ca. 18 times) higher stability after 3000 s of continuous electrolysis. The observed enhancement was proven to originate from driving the reaction mechanism principally to the desirable direct dehydrogenation pathway on the expense of the poisoning dehydration path. The impedance and CO stripping measurements confirmed the prevailing of both the electronic and third body effects in the catalytic enhancement.